Prospective study on outcome of MDR-TB using the shorter regimen during COVID-19 pandemic - G Sravan Kumar; P Sameena; V Karthik; Nalini Ghanate (Journal of Family Medicine and Primary Care)
Background: According to Indian TB report 2020, 66,225 MDR/RR-TB cases were detected in India, 56,569 (85%) were put on treatment, and 40,397 (75%) were initiated on shorter drug regimens at the time of diagnosis. In the absence of an effective vaccine, there is an urgent need for new treatment regimens, drugs, and diagnostics to slow the evolution of drug resistance and limit transmission of resistant variants, as well as to ameliorate the treatment outcome of patients infected with MDR/XDR M. tuberculosis strains. Aim: To evaluate the efficacy of a shorter drug regimen in MDR-PTB and estimate the adverse effects of drugs used in the regimen. Methods: This is an institution-based prospective study which included 135 confirmed MDR-PTB patients. Patients with extra-pulmonary MDR-TB and use of SLI for more than one month were excluded. Results: The success rate using a shorter regimen was 65.2% which is respectable, given the COVID-19 pandemic considered during the study period. Minor adverse events such as nausea (39.3%) and vomiting (34.8%) were reported. Rare adverse effects such as hearing loss (8.9%) and hypothyroidism (0.2%) were also seen in the study population. Conclusion: Overall treatment success was similar when compared to other studies done previously. A shorter drug regimen was associated with minor adverse effects such as gastrointestinal adverse effects such as vomiting and hearing loss observed in elderly patients. Baseline unknown drug resistance and lower BMI were associated with unsuccessful outcomes. Measures should be taken to improve nutrition. Our results argue the need for improving baseline DST at peripheral areas in order to effectively evaluate resistance to other drugs, especially in settings with high levels of first and second-line drug resistance.